Brief report: Older adolescents and young adults may be at higher risk for changes to menstrual cycle length with COVID-19 vaccination - Laura A. Payne; Alison Edelman; Blair G. Darney; Eleonora Benhar; Emily R. Boniface (PLoS ONE, 2025)
Existing research has consistently demonstrated that adult women experience a small temporary increase in menstrual cycle length following COVID-19 vaccination; however, less is known about whether these changes differ depending on age. The purpose of this study was to assess differences in menstrual cycle length in older adolescent and adult women following an initial COVID-19 vaccine dose compared to an unvaccinated control group, with all analyses conducted across four separate age groups (18–24, 25–29, 30–34, and 35–45). Participants with menstrual cycles averaging 24–38 days prior to vaccination prospectively tracked menstrual cycles using the fertility awareness application Natural Cycles. We compared the within-individual change in menstrual cycle length pre- to post-vaccination in the vaccination group and across four consecutive menstrual cycles in the unvaccinated group, by age. Results demonstrated a 1.11 day adjusted increase in menstrual cycle length for adolescents and young adults (AYAs; ages 18–24), relative to unvaccinated individuals in that age range, while the three older groups all experienced less than a one-day post-vaccination adjusted increase in cycle length compared to their unvaccinated counterparts. These data show that, while COVID-19 vaccination was associated with longer menstrual cycle length for all groups overall, greater increases in menstrual cycle length were observed in AYAs. This suggests that younger individuals are more susceptible to menstrual cycle changes following COVID-19 vaccination.